Pengaruh Kebijakan Dividen Terhadap Pertumbuhan Laba - Lakoro, Febriyanti; Junus, Onong; Rahman, Zubaidah (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
This research aims to determine the effect of dividend policy on profit growth. This is a quantitative study with an explanatory type of research that explains the relationship or influence between variables. The population in this study consists of 6 cosmetics and household goods companies for the period 2018-2022, with 30 financial report data points. The sampling method used is saturated sampling. This research uses secondary data obtained from the annual financial reports of cosmetics and household goods companies listed on the Indonesia Stock Exchange for the period 2018-2022. The data analysis method used in this research is simple linear regression. The independent variable in this research is the Dividend Policy. The dependent variable in this research is Profit Growth. Based on the analysis results, it shows that simultaneously, the Dividend Policy does not affect Profit Growth.